1980
DOI: 10.1111/j.1532-5415.1980.tb00514.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagonal Ear Lobe Crease and Coronary Risk Factors

Abstract: The prevalence of ear lobe crease (ELC) was determined in 421 patients with myocardial infarction (MI) and in 421 controls. A higher prevalence (p less than 0.05) of ELC was found in MI patients (77 percent) in comparison to controls (40 percent), regardless of age. In addition, a higher prevalence was found in patients in whom MI was combined with diabetic retinopathy or hypertension, and in Ashkenazi Jews compared to non-Ashkenazi Jews. Ear lobe biopsies in 12 subjects revealed tears of the elastic fibers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 12 publications
2
62
0
2
Order By: Relevance
“…20,21 In contrast, atherosclerotic changes in the arterial wall could include smooth muscle cell proliferation, deposition of lipid and accumulation of collagen, elastin and proteoglycans, without the compensatory development of scar collagen. Changes in the ratio of collagen to elastin have been known to structurally affect the elastic behavior of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 In contrast, atherosclerotic changes in the arterial wall could include smooth muscle cell proliferation, deposition of lipid and accumulation of collagen, elastin and proteoglycans, without the compensatory development of scar collagen. Changes in the ratio of collagen to elastin have been known to structurally affect the elastic behavior of the arterial wall.…”
Section: Discussionmentioning
confidence: 99%
“…15 Many other investigators have also reported similar findings. 11,13,14,19,20,25 Studies have shown that ELC has a reasonably high predictive value for cardiac events. 15 ELC and atherosclerotic cardiovascular disease in metabolic syndrome patients.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Moreover, ELC has also been found to be a marker not only of CAD, but also of generalized atherosclerosis. 15,16 However, the lack of a theoretical foundation for a causal relationship between ELC and atherosclerosis inhibits the clinical value.…”
mentioning
confidence: 99%
“…DKLÇ hakk›ndaki daha önceki çal›flmalar gözden geçi-rildi¤inde, büyük ço¤unlu¤unun klini¤e dayand›¤› ve ço-¤unlukla DKLÇ ile kardiyovasküler hastal›klar aras›nda-ki iliflkinin araflt›r›ld›¤› ortaya ç›kmaktad›r (6). Bununla birlikte, koroner arter hastal›¤›n›n bilinen risk faktörle-rinden yafl, cinsiyet, hipertansiyon, diabetes mellitus, hiperlipidemi ve obesite ile DKLÇ aras›ndaki iliflkiler de araflt›r›lm›fl, risk faktörlerinden baz›lar›nda anlaml› iliflkiler bildirilmiflken (2,4,(6)(7)(8)(9)(10)(11)(12)(13)(14) baz›lar›nda ise iliflki saptanmam›flt›r (2,3,5,6,8,(15)(16)(17)(18)(19)(20)(21).…”
Section: G‹r‹fiunclassified
“…Benzer bir postmortem çal›flmada Kirkham ve arkadafllar› (18), kardiyovasküler sebepli ölümler ile DKLÇ aras›nda iliflki oldu¤u sonucuna varm›fllard›r. Çal›flmam›z›n bulgular›, vakalara uygulanan anjiografiler sonucunda RIA, RC ve ACD'de saptanan daralma yüzdeleri artt›kça DKLÇ görülme s›kl›¤›n›n artt›¤›n› göstermekte olup DKLÇ ve koroner arter hastal›¤› aras›nda anlaml› iliflkiler bildiren * Sat›r yüzdesi ** Sütun yüzdesi daha önceki çal›flmalar›n bulgular› ile uyumludur (2,3,4,8,9,13,14,20,(24)(25)(26)(27)(28). Baz› araflt›r›c›lar bu iliflkiyi yalanlamakta ve yafl›n, ço¤unlukla yafll› kiflilerde bulunan DKLÇ'nin ortaya ç›k›fl›n› etkileyebilece¤i üzerinde durmaktad›rlar (5,10,16,17,(29)(30)(31).…”
Section: Tartifimaunclassified